Small Medium Contractor Enterprises (Smces) In Malaysia: Investigating The Impact Of Core Competencies And Financial Support On Project Success - Ali, Zamri (2012)
The purpose of this study is to investigate the relationship of core competencies which is entrepreneurial competence, technical competence, evaluative competence and relational competence and financial support on success of the project among small and medium contractor enterprises (SMCEs) in Malaysia.